Experiences from implementation of internet-delivered cognitive behaviour therapy for insomnia in psychiatric health care: a qualitative study applying the NASSS framework - Josefin Kadesjö Banck; Susanne Bernhardsson (BMC, 2020)
Abstract Background Insomnia is a common diagnosis among patients in psychiatric health care and effective treatments are highly demanded. Previous research suggests that internet-delivered cognitive behavioural therapy for insomnia (ICBT-i) is helpful for a variety of patients and may be effective for psychiatric health care patients. Little is known about implementation of ICBT-i in psychiatric health care. The aim of this study was to explore experiences among therapists and managers who participated in a pilot implementation of ICBT-i in outpatient psychiatric health care, and to identify determinants for the implementation. Methods Semi-structured interviews were conducted with 7 therapists and 5 managers working in outpatient psychiatric health care and directly involved with the pilot implementation. Data were analysed using qualitative content analysis guided by the NASSS framework, combining inductive and deductive approaches. Results The analysis revealed 32 facilitators, 21 barriers, and 2 determinants that were both a barrier and a facilitator, organised in 1-5 themes under each of the 7 NASSS domains. Key facilitators included: meeting a demand for treatment options with the ICBT-i programme, the experienced benefits of ICBT-i as a treatment option for insomnia, training and support, engagement and support from managers and the wider system, and a long-term organisation for maintenance of the technology. Key barriers included: low interest in ICBT-i among therapists, difficulty in recruiting patients, perceived low ability in therapists to deliver treatment online, technical problems, and therapists' competing demands leading to low priority of ICBT-i. Complexity analysis assessed two NASSS domains as simple, four as complicated, and one as complex. Conclusions The study contributes new knowledge and insights into the implementation process of ICBT-i in psychiatric health care. Our findings highlight the importance of providing training, support, and guidance in online treatment for therapists when implementing a technological innovation. Technical problems should be minimised and the maintenance and demand-side value for the technology must be clear. Support from managers at all levels is crucial, particularly support to therapists in everyday prioritisation among competing demands. Besides taking the identified determinants into account, managing complexity is important for successful scale-up implementation.